The impact of e-Health interventions on promoting Self-Care in Chronic Patients: an Umbrella Review. (30th September 2020) - Renzi, E; Gasperini, G; Baccolini, V; Marzuillo, C; De Vito, C; Villari, P; Massimi, A
Abstract: Background: Promoting self-care is one of the most promising strategies to manage people with chronic conditions and to improve the Public Health System resilience. In this context, the use of e-Health could facilitate self-care promotion, assure continuity of care and save time. Methods: We performed an umbrella review on Cochrane, Scopus, Medline, PsychInfo, CINAHL to analyse e-Health self-care promoting intervention in patients with Type- 2 Diabetes Mellitus (T2DM), Cardiovascular Diseases (CVD) and Chronic Obstructive Pulmonary Disease (COPD) compared to traditional intervention. AMSTAR-2 was used for quality appraisal. Results: 10 systematic reviews were included for an amount of 376 RCTs and 3 quasi-experimental studies. All the e-Health interventions retrieved were categorized in 4 subgroups: Phone Reminder, Telemonitoring, Psychoeducational intervention supported by PCs/Apps and Combined Intervention. Nurses (271/379 studies) and physicians (149/379 studies) were the healthcare workers mostly involved in the administration of e-Health interventions. T2DM (5 reviews; 175 studies) and CVD (7 reviews; 164 studies) patients gained more progresses in self-management than COPD patients (3 reviews; 8 studies). E-Health appeared effective both in promoting self-management and disease awareness. Globally, all the e-Health interventions seemed to improve Quality of Life and clinical outcomes. Phone reminders were most effective to increase Medication Adherence. All Causes Mortality registered a positive effect through Telemonitoring. Hospital Admission and Cost-Efficacy were explored only by telemonitoring and it did not show differences with traditional intervention. Conclusions: E-Health is an effective strategy to promote self-care in patients with chronic conditions and to improve quality of life and clinical outcomes. Further research is required to test e-Health intervention in COPD patients and to examine if there is different efficacy among e-Health subgroups. Key messages: E-Health should be integrated in Primary Care strategies to improve Public Health systems resilience. Nurses, as frontline Primary Health Care workers, should be advised for e-Health administration.